2007
DOI: 10.1007/s10856-007-3112-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the composite surface sealant application moment on marginal sealing of compactable composite resin restoration

Abstract: An analysis was carried out to observe whether the application or not of a composite surface sealant (CSS), as well the moment for CSS application were able to reduce marginal microleakage in compactable composite resin restoration. All the preparations were restored with a compactable composite resin. The restored teeth were randomly assessed. G1 (control group): finished and polished; G2: finished, polished, etched and cover with CSS; G3: immediately after the restoration done the CSS was applied, then finis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…The advantages of co-polymerizing the two materials may be related to enhancing the bond and reducing restoration finishing time. 7 In general, this technique is more applicable to medium to small restorations, where reshaping and recontouring can be achieved before light-curing, such as class V, small class I, lingual class III, and even in the margin of indirect restorations on the top of unpolymerized resin cement after the removal of excess material. There is a lack of data reporting composite properties when sealants are co-polymerized with the last increment of resin.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of co-polymerizing the two materials may be related to enhancing the bond and reducing restoration finishing time. 7 In general, this technique is more applicable to medium to small restorations, where reshaping and recontouring can be achieved before light-curing, such as class V, small class I, lingual class III, and even in the margin of indirect restorations on the top of unpolymerized resin cement after the removal of excess material. There is a lack of data reporting composite properties when sealants are co-polymerized with the last increment of resin.…”
Section: Introductionmentioning
confidence: 99%
“…The complex nature of the gingival area and was in agreement with our study, whereby decreased permeability and increased sealing ability at the enamel margins (occlusal) can be responsible for this result. [12,39,49] This design may not accurately simulate intra-oral conditions. It is suggested that this study be followed by other research that evaluates the influence of other kinds of desensitizers applied at different times on various types of restoration material interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[1,15] Surface sealants, applied over the cavosurface margins of the finished restorations, penetrate to the structural microdefects formed during finishing and polishing procedures and the marginal gaps by capillary action. [1,7,14,16] Hence, this effect can reduce microleakage by improving marginal sealing. In vitro studies have revealed that low viscosity, high flow rate, and high wettability properties are important requirements to provide the penetration (fluidity) onto material subsurface microstructure and good clinical performance for surface sealants.…”
Section: The Effect Of Surface Sealants With Different Filler Contentmentioning
confidence: 99%
“…While some of these studies indicated that the application of surface sealants effectively decreased microleakage, [14,[21][22][23] some of them reported that the application of surface sealants could not eliminate microleakage completely. [1,7,16] Consequently, it is recommended that further studies should be conducted to evaluate new materials and ensure the effects of these materials on microleakage with the aim of confirming the use of these materials in clinical routine. To the best of our knowledge, no information is available in the literature regarding the effect of surface sealants with different filler content on microleakage of resin restorations.…”
Section: The Effect Of Surface Sealants With Different Filler Contentmentioning
confidence: 99%